Software engineering process - Oshana, Rob (IEEE, 2011)
This tutorial is part of a series of eLearning courses designed to help you prepare for the examination to become a Certified Software Development Professional (CSDP) or to learn more about specific software engineering topics. Courses in this series address one or more of the fifteen Knowledge Areas that comprise the Software Engineering Body of Knowledge - or SWEBOK, upon which the Certification Exam is based. Within each course module, there is a list of textbooks, courses and relevant reference materials to assist you in preparing for the Certification Exam. The Software Engineering Process KA can be examined on two levels. The first level encompasses the technical and managerial activities within the software life cycle processes that are performed during software acquisition, development, maintenance and retirement. The second is the meta-level, which is concerned with the definition, implementation, assessment, measurement, management, change and improvement of the software life cycle processes themselves. The first level is covered by other KAs in the CSDP Assessment program. This KA is concerned with the second. This course is intended to assess your understanding of the software engineering process through inline quizzes and feedback. Specific topics addressed in this course are: process implementation and change, process definition, process assessment, measurement and software process tools